Synthesis and crystal structure of ethyl (2S,4aS,6aS,6bR,8aR,12aS,12bR,14bR,E)-10-(((3,4-dichlorobenzyl)oxy)imino)-2,4a,6a,6b,9,9,12a-heptamethyl-13-oxo-1,2,3,4,4a,5,6,6a,6b,7,8,8a,9,10,11,12,12a,12b,13,14b-icosahydropicene-2-carboxylate - Dong Zhang-Chao; Shen Hui; Mu Ze-Bo; Xu Kai-Hua (Zeitschrift für Kristallographie - New Crystal Structures)
C39H53Cl2NO4, monoclinic, P21 (no. 4), a = 7.55730(10) Å, b = 11.0989(2) Å, c = 20.9222(3) Å, β = 91.426(1)°, V = 1754.36(5) Å3, Z = 2, Rgt(F) = 0.0360, wRref(F2) = 0.1028, T = 169.98(10) K.